Hukum Ar-Rahn Dalam Islam - Irfan Syuhudi; Ahmadih Rojalih Jawab (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
All areas of human life have been regulated by the establishment of perfect laws by the Most Perfect Allah through His messenger Prophet Muhammad according to human nature for the good of life in the world and safety in the hereafter. The religion of Islam is not only a spiritual need, but also a way of life, namely the way or way of human life in the world. One example of Islamic law that has been perfectly established in human life is Ar-Rahn, which is a collateral item that is retained with a function as a pawn due to debt and credit which aims to provide peace and harmony between the debtor and the debtor. There are 2 forms of pawnshop institutions in Indonesia, namely sharia pawnshops and conventional pawnshops with many brands and names of these institutions. And the original law of pawnshop (Ar-Rahn) in Islam is permissible, but in many cases of practice there are things that change the law to haram. Meanwhile, the permissibility of Rahn or Pawnshop is one proof of Allah's mercy and compassion as a solution of convenience for some of His servants who feel their economy or life needs are unstable and in dire need. This makes it interesting to see further how the correct practice of pawnshop (Ar-Rahn) according to the guidance of the Prophet as a benchmark or guide in practicing it today.